Client and therapist initial experience of using mindfulness in therapy - Horst, Kyle; Newsom, Kimmery; Stith, Sandra M. (My University, 2013)
Literature has demonstrated the influence of mindfulness practice on both clients and therapists; however, no literature has considered the experience of mindfulness in therapy from both members of the therapeutic dyad. The present study interviewed five separate therapy dyads (n=10) regarding their experience of first using mindfulness in session. Participants, both clients and therapists, had little-to-no experience with mindfulness prior to the study. Interview transcripts were analyzed and common themes were derived. Results indicated that both clients and therapist felt that the practice of mindfulness had an impact on the therapeutic relationship. Furthermore, participants also suggested ways in which therapists may better utilize mindfulness in therapy.
Keywords: Mindfulness; Therapy dyad; Therapeutic relationship; Client experience